Highly Polarized Coumarin Derivatives Revisited: Solvent‐Controlled Competition Between Proton‐Coupled Electron Transfer and Twisted Intramolecular Charge Transfer. Issue 32 (20th May 2020) - Morawski, Olaf W.; Kielesiński, Łukasz; Gryko, Daniel T.; Sobolewski, Andrzej L.
Abstract: Linking a polarized coumarin unit with an aromatic substituent via an amide bridge results in weak electronic coupling that affects the intramolecular electron‐transfer (ET) process. As a result of this, interesting solvent‐dependent photophysical properties can be observed. In polar solvents, electron transfer in coumarin derivatives of this type induces a mutual twist of the electron‐donating and ‐accepting molecular units (TICT process) that facilitates radiationless decay processes (internal conversion). In the dyad with the strongest intramolecular hydrogen bond, the planar form is stabilized, such that twisting can only occur in highly polar solvents, whereas a fast proton‐coupled electron‐transfer (PCET process) occurs in nonpolar n ‐alkanes. The k PCET rate constant decreases linearly with the energy of the fluorescence maximum in different solvents. This observation can be explained in terms of competition between electron‐ and proton‐transfer from a highly polarized (ca. 15 D) and fluorescent locally excited ( 1 LE) state to a much less polarized (ca. 4 D) charge‐transfer ( 1 CT) state, a unique occurrence. Photophysical measurements performed for a family of related coumarin dyads, together with results of quantum‐chemical computations, give insight into the mechanism of the ET process, which is followed by either a TICT or a PCET process. Our results reveal that dielectric solvation of the excited state slows down the PCET process, even in nonpolar solvents. Abstract : Solvent‐dependent photophysics : A solvent‐modulated competition between PCET and TICT processes occurs in amido‐coumarins. This stems from the following: 1) electron transfer occurring in the excited state neutralizes the charge distribution, resulting in the charge‐transfer state possessing a low dipole moment and 2) the charge‐transfer state is stabilized by either proton transfer or mutual twist of electron‐donating and ‐accepting molecular moieties (see figure).